The cost of disinflation in a small open economy vis-à-vis a closed economy - Oleksandr Faryna; Magnús Jónsson; Nadiia Shapovalenko (Sveriges Riksbank, 2021)
We use a standard new Keynesian model to evaluate the cost of disinflation - measured by the sacrifice ratio, the central bank's loss function, and the welfare cost - in a small open economy vis-à-vis a closed economy. Disinflation is either more costly or less beneficial in the small open economy, but the results vary quantitatively depending on the measure and the economic environment. Optimised simple monetary policy rules imply that the relative weight on inflation stabilisation should be lower in the small open economy if the central bank minimises the loss function, but higher if it maximises welfare.
Keywords: E31; E5; F41; 330; Disinflation; sacrifice ratio; central bank's loss function; welfare cost; small open economy; new Keynesian model; optimised rules; imperfect credibility